Aclidinium bromide/formoterol fixed-dose combination therapy for COPD: the evidence to date - Moitra S; Bhome AB; Brashier BB (Dove Medical Press, 2015)
Subhabrata Moitra,1 Arvind B Bhome,2 Bill B Brashier1 1Chest Research Foundation, Pune, Maharashtra, India; 2Indian Coalition of Obstructive Lung Diseases (ICOLD) Network, Pune, Maharashtra, India Abstract: The quest for the right combination of bronchodilators with different mechanisms of action such as long-acting muscarinic antagonists and long-acting β-agonists in the management of stable moderate-to-severe chronic obstructive pulmonary disease (COPD) is a topic of intense research activity currently, given the rising morbidity and mortality due to this disease. The fixed-dose combination of aclidinium bromide and formoterol fumarate in a single inhaler seems to offer superior advantages over either drugs given alone or as separate inhalers concurrently. Since the fixed-dose combination needs to be given twice daily, it is likely to achieve control of symptoms most crucial to the quality of life in COPD, namely, the morning hours. This is reflected in significant trough FEV1 (forced expiratory volume in 1 second) improvements after the dose. This paper reviews the various studies related to this combination put in the perspective of its safety and efficacy and potential benefits over other therapeutic options. However, there is a dearth of data on the long-term safety and efficacy in terms of improvement in lung function. This combination could emerge as an excellent option in the management of stable COPD if data on exacerbation rates and patient-reported outcomes become available from longer-term studies. Moreover, we need some more studies to define the ideal phenotype of COPD best suited for the use of this combination. Keywords: aclidinium, formoterol, COPD, lung function, bronchodilators, combination therapy